Cell wall composition and biomass saccharification potential of Sida hermaphrodita differ between genetically distant accessions - Schrey, Silvia D.; Martinez Diaz, Jimena; Becker, Lukas; Mademann, Jane A.; Ohrem, Benedict; Drobietz, Dagmar; Chaloupsky, Pavel; Jablonowski, Nicolai D.; Wever, Christian; Grande, Philipp M.; Pestsova, Elena; Klose, Holger (Frontiers in Plant Science, 2023)
Due to its ample production of lignocellulosic biomass, Sida hermaphrodita (Sida), a perennial forb, is considered a valuable raw material for biorefinery processes. The recalcitrant nature of Sida lignocellulosic biomass towards pretreatment and fractionation processes has previously been studied. However, Sida is a non-domesticated species and here we aimed at expanding the potential of such plants in terms of their processability for downstream processes by making use of the natural variety of Sida. To achieve this goal, we established a collection comprising 16 different Sida accessions obtained from North America and Europe. First, we asked whether their cell wall characteristics are reflected in genetic distance or geographical distribution, respectively. A genotyping-by-sequencing (GBS) analysis resulting in a phylogenic tree based on 751 Single Nucleotide Polymorphisms (SNPs), revealed a high genetic diversity and a clear separation between accessions collected in North America and Europe. Further, all three North American accessions were separated from each other. Of the eleven European accessions, five form individual groups and six others belong to a single group. Clonal plants of seven selected accessions of American and European origin were produced and cultivated under greenhouse conditions and the resulting plant material was used for in-depth wet-chemical and spectroscopic cell wall characterization. Two accessions with contrasting cell wall characteristics were then selected and processed using the OrganoCat technology. Results of the different product yields and chemical compositions are reported. Overall, cell wall analyses revealed contrasting clusters regarding these main components between the accessions that can be related to genetic and, partly, geographical distance. Phenotypically, the accessions clustered into two groups that are not entirely overlapping with geographical origin. These results can be the basis for a targeted selection or cultivation of Sida accessions for biorefinery approaches.